Probe pulse design in Brillouin optical time‐domain reflectometry. Issue 6 (10th October 2022) - Li, Mupeng; Xu, Tianhua; Wang, Shuang; Hu, Wenxiu; Jiang, Junfeng; Liu, Tiegen
Abstract: Brillouin optical time‐domain reflectometry (BOTDR) is a branch of distributed fibre‐optic sensors, and it can measure the strain and the temperature information, localised by the return time of the probe pulse, along the fibre based on the spontaneous Brillouin scattering process. Parameters of the BOTDR system, including the spatial resolution, the signal‐to‐noise ratio, the measurement speed, and the sensing range, have a mutually restrictive relationship. In order to improve the performance of the BOTDR system, researchers have focussed on improving the design of the probe pulse, for example, transforming the shape, the sequence, and the spectral properties of the pulse. This study summarises the recent progress in the design of detection pulses in BOTDR systems, and comprehensively demonstrates the improvement effects of various pulse modulation formats on the system performance.